THE ROLE OF RESILIENCE AND PSYCHOLOGICAL WELL-BEING TOWARDS PARENTING STRESS OF MOTHERS OF CHILDREN WITH SPECIAL NEEDS IN SPECIAL SCHOOLS IN SIDOARJO - Ashil Rizal Achmad Yani; Laili, Nurfi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to determine whether there is a relationship between resilience and psychological well-being concerning parenting stress in mothers with children with special needs. Method: The research employs a correlational study with a quantitative approach. The population for this study consists of mothers with children with special needs in Sidoarjo, specifically those whose children attend Special Needs Schools. The sampling technique used is a composite sampling method based on Cochran's formula, with a sample size of 76 participants. The measurement tools used in this study are the Brief Resilience Scale (BRS) for resilience, the Psychological Well-Being 18 Scale by Ryff (PWB) for psychological well-being, and the Parental Stress Scale (PSS) for parenting stress. The data analysis technique employed is multiple regression analysis. Results: The results of this study indicate that, collectively, resilience and psychological well-being have a significant impact on parenting stress among mothers with children with special needs. Novelty: This study highlights the dual role of resilience and psychological well-being as combined predictors of parenting stress specifically in mothers with children with special needs, a population that has received limited attention in psychological correlational research.